The Oregon experiment re-examined: the need to bolster primary care. (20th October 2014) - Heintzman, John; Gold, Rachel; Bailey, Steffani R; DeVoe, Jennifer E
Abstract : John Heintzman and colleagues use less publicized evidence from Oregon to argue that unless access to primary care is improved, the benefits of widening the eligibility for public health insurance on individual and population health will be limited